2022
DOI: 10.1002/aic.17711
|View full text |Cite
|
Sign up to set email alerts
|

Novel process for selective separation of trace artemisitene from artemisinin by ammonium functional ionic liquids

Abstract: One of the challenges to obtain high‐quality natural active substances is the selective separation of the target compound from its analogues. In this study, ionic liquids (ILs), with design flexibility, were proposed to separate artemisitene and artemisinin, typical examples of natural analogues. Based on COSMO‐RS calculation, several ILs were selected to separate artemisitene/artemisinin by experiment. It was demonstrated that the aqueous solution of N‐allyl‐N,N,N‐trimethylammonium chloride ([AA][Cl]) exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…However, in the systems containing copolymerized ILs, the concentration of ARE in the extraction phase (the PIL phase), D ARE and S ARE/ART , increased with the increase of IL content in the copolymerized IL. The good separation efficiency could be attributed to π–π complexation between the copolymerized IL and ARE as illustrated in our previous work by spectroscopic analysis and simulation . Besides, we also illustrated that hydrogen bonding between the copolymerized IL and ARE (Figure S11, Supporting Information) also plays a role in this separation process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, in the systems containing copolymerized ILs, the concentration of ARE in the extraction phase (the PIL phase), D ARE and S ARE/ART , increased with the increase of IL content in the copolymerized IL. The good separation efficiency could be attributed to π–π complexation between the copolymerized IL and ARE as illustrated in our previous work by spectroscopic analysis and simulation . Besides, we also illustrated that hydrogen bonding between the copolymerized IL and ARE (Figure S11, Supporting Information) also plays a role in this separation process.…”
Section: Resultsmentioning
confidence: 99%
“…The standard curves and methods for quantitative determination of ARE and ART concentrations by HPLC followed our previous study …”
Section: Experimental and Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…[25][26][27] Recent work has demonstrated that ILs containing specific anions and cations can recognize even subtle structural motifs such as hydroxyl groups, 28,29 aromatic rings, 30 and chirality, 31,32 successfully separating various isomers, homologues, and stereoisomers. 6,[33][34][35] However, the vast majority of studies focus solely on the rational molecular design of the IL extractant through systematic variation of anion, cation, and alkyl chains. [36][37][38] The potential synergistic effects of strategically designing the feedstock solvent along with the IL have been largely ignored.…”
Section: Introductionmentioning
confidence: 99%